(untitled) (Physical Education, Health and Social Sciences, 2025)
To improve the sustainability of building materials, this study explores the use of sodium chloride (NaCl) in concrete mixtures as a partial substitute for cement. The study examines the various ways that salt affects concrete, taking into account how it affects durability, long-term structural integrity, and early strength development. Over time, chloride ions from NaCl may seep through the cement matrix and cause embedded steel reinforcement to corrode. However, NaCl can speed up hydration and encourage the production of calcium silicate hydrate (C-S-H) at ideal dosages (usually less than 5% by weight of cement), which improves early-age compressive strength. To maximize the advantages of quicker setting without sacrificing long-term performance, a careful balance is essential when adding salt to concrete. It is crucial to assess the intended use, exposure conditions in the environment, and the existence of reinforcement. Strategies for adding salt that optimize performance while addressing durability issues are still being investigated, especially for non-structural or short-life applications with low corrosion threats.